ELECTROMAGNETIC PUSHKA MODEL TO CREATE RECOMMENDATIONS AND SUGGESTIONS - Савридинов Н.; Нажимидинов З. Ш.; Мовланов Д. Н. (Bright Mind Publishing, 2025)
The thesis demonstrates model structure of the electromagnetic canon, it’s working process and physic procedures in it’s elements.
Keywords: Capacity, capability, electric key, power, unpower, electr source.